"Active and Conscious Builders of Communism": State-Sponsored Tourism for Soviet Adolescents in the Early Cold War, 1945–53. (1st September 2014) - Tsipursky, Gleb
Abstract: This article examines state-sponsored tourism for Soviet adolescents during the post-World War II years of Stalin's rule, 1945–1953, a topic not explored in any depth within scholarship on the USSR, despite the surprising degree of importance ascribed to this area by the authorities. Through adopting the lens of tourism studies and childhood and youth studies, the essay enriches our understanding of Soviet postwar society, particularly the overt official endeavors to forge model young citizens and the covert efforts to legitimize the political system, encourage natalism, and spread the Soviet model throughout the world via Cold War public diplomacy. Finding striking convergences and illuminating disparities between the approaches of different political and social structures to young people and their leisure time, this piece advances our understanding of the ways that modern societies maintain and reproduce themselves, or fail to do so. Furthermore, the essay considers matters of broader humanistic relevance, such as the mobilization of emotions for government purposes and the politicization of childhood and youthhood. It compares the Soviet case study to authoritarian and democratic western states and uses the socialist context of the postwar Soviet Union to enrich and add nuance to current scholarly models, based overwhelmingly on case studies of western settings that undercount the importance of state organs.